PENSION PROVISION FOR DIPLOMATIC EMPLOYEES: REGULATORY AND LEGAL PREREQUISITES AND IDENTIFICATION OF CURRENT DEVELOPMENT ISSUES - Tursunova M. U. (Scholar Express Journals, 2023)
This scientific article elaborates the necessity of addressing the issues related to the pension provision for diplomatic employees, specifically their legislative regulation in the Republic of Uzbekistan through specialized normative and legal acts. It should be noted that the absence of normative and legal foundations and clarity in regulating the pension provision for diplomatic employees can create uncertain situations, lead to legal disputes, and the high degree of confidentiality of relevant information hinders scientific research, analysis, and examination. The author concludes that there is a need to change the normative, legal, and scientific approaches to the posed question in favor of ensuring legal clarity, publicity, and transparency, as diplomatic service is a type of public service that is becoming increasingly relevant and in demand in any state
Keywords: pension; social welfare; work experience